Import competition and firm-level CO emissions: Evidence from the German manufacturing industry - Jakob Lehr (Canadian Journal of Economics/Revue canadienne d'économique, 2025)
Using the German census of the manufacturing industry, I analyze the impact of import competition on carbon emissions per unit of deflated sales (emission intensity). I combine precise information on firm-level CO emissions with sector-level trade flows. Looking at the period 1995 until 2017, I focus on the impact of the rise of Eastern Europe and China while addressing the endogeneity of trade flows with an instrumental variable approach. The baseline results suggest that a 1~pp increase in the import penetration ratio caused a reduction of the average firm's emission intensity by approximately 0.3%. This result implies that the rise of the joint East between 1995 and 2017 kept the average firm's emission intensity 6% below the level it would have had in the absence of the East's rise. I do not find strong indication for reallocation of production towards more efficient firms. Finally, I supplement the analysis by examining the effect of export opportunities due to the East's rise. The results indicate that exporting to the East increased sales and emissions, with a small, if any, negative effect on emission intensities.
Keywords: 330